2006
DOI: 10.1120/jacmp.2027.25372
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characteristics of a new linear accelerator under gated operation

Abstract: Respiratory gated radiotherapy may allow reduction of the treatment margins, thus sparing healthy tissue and/or allowing dose escalation to the tumor. However, current commissioning and quality assurance of linear accelerators do not include evaluation of gated delivery. The purpose of this study is to test gated photon delivery of a Siemens ONCOR Avant-Garde linear accelerator. Dosimetric characteristics for gated and nongated delivery of 6-MV and 15-MV photons were compared for the range of doses, dose rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Gating is initiated with different respiratory monitoring systems at the moment and various studies have been performed in order to assess the differences between them [ 8 - 11 ]. Several others additionally investigated the question whether or not a linac is able to being gated, [ 3 ] or the linac’s performance under gated treatment [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gating is initiated with different respiratory monitoring systems at the moment and various studies have been performed in order to assess the differences between them [ 8 - 11 ]. Several others additionally investigated the question whether or not a linac is able to being gated, [ 3 ] or the linac’s performance under gated treatment [ 12 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors have reported gating results for three manufacturers: Varian Wang 2000 andJin andYin 2005); Siemens (Kriminski et al 2006 andWeibert et al 2009) and Brainlab (Hugo et al 2003 andVerellen et al 2003). The Varian system uses a gridded gun for gating.…”
Section: Introductionmentioning
confidence: 99%
“…There are different sorts of algorithms to predict dosimetric portal images ͑DPIs͒. 4,[12][13][14][15][16][17][18][19][20][21] Among them, Monte Carlo ͑MC͒ simulation is highly attractive given its ability to accurately reproduce measurements. It has been demonstrated that MC is able to achieve agreement between the predicted and measured DPIs.…”
Section: Introductionmentioning
confidence: 99%